Birth defects data from hospital-based birth defect surveillance in Guilin, China, 2018–2020 - Yang, Xingdi; Zeng, Jianjuan; Gu, Yiping; Fang, Yiming; Wei, Caiyun; Tan, Shengkui; Zhang, Xiaoying (Frontiers in Public Health, 2022)
Objectives: Birth defects (BDs) are a major contributor to perinatal and infant mortality, morbidity and lifelong disability worldwide. A hospital-based birth defects study was implemented in Guilin city in the Guangxi province of Southwestern China between 2018 and 2020. This study aimed to determine the prevalence of BDs in the studied region, and the classification of BDs based on clinical presentation and causation. Methods: The study involved BDs among all pregnancy outcomes (live births, stillbirths, death within 7 days, and pregnancy terminations) born in the 42 registered hospitals of Guilin between 2018 and 2020. The epidemiological characteristics of BDs and the etiologic profile of BDs were evaluated in this study. Results: Of the total 147817 births recorded during the study period, 2003 BDs were detected, giving a total prevalence rate of 13.55‰. The top five BD types were congenital heart defects, polydactyly, syndactyly, malformations of the external ear, and talipes equinovarus, whereas, neural tube defects, congential esophageal atresia, gastroschisis, extrophy of urinary bladder, were the least common BD types in these three years. Only 8.64% of cases were assigned a known etiology, while most cases (91.36%) could not be conclusively assigned a specific cause. Conclusion: This study provides an epidemiological description of BDs in Guilin, which may be helpful for understanding the overall situation in Southwest China and broadening the classification of BDs according to the etiology.